Ceres's obliquity history and its implications for the permanently shadowed regions. Issue 6 (22nd March 2017) - Ermakov, A. I.; Mazarico, E.; Schröder, S. E.; Carsenty, U.; Schorghofer, N.; Preusker, F.; Raymond, C.A.; Russell, C. T.; Zuber, M. T.
Abstract: Due to the small current obliquity of Ceres ( ε ≈4°), permanently shadowed regions (PSRs) exist on the dwarf planet's surface. Since the existence and persistence of the PSRs depend on the obliquity, we compute the obliquity history over the last 3 Myr and find that it undergoes large oscillations with a period of 24.5 kyr and a maximum of ε m a x ≈19.6°. During periods of large obliquity, most of the present‐day PSRs receive direct sunlight. Some craters in Ceres's polar regions possess bright crater floor deposits (BCFDs). We find an apparent correlation between BCFDs and the most persistent PSRs. In the north, only two PSRs remain at ε m a x and they both contain BCFDs. In the south, one of the two only craters that remain in shadow at ε m a x contains a BCFD. The location of BCFDs within persistent PSRs strongly suggests that BCFDs consist of volatiles accumulated in PSR cold traps: either water molecules trapped from the exosphere or exposed ground ice. Key Points: Currently, Ceres obliquity is only 4°; we have calculated Ceres obliquity history and found that it undergoes large periodic oscillations At higher obliquities, only few PSRs remain; we find a correlation between persistent PSRs and bright crater floor deposits Bright deposits in PSR craters are likely volatiles accumulated in cold traps: water molecules from the exosphere or exposed ground ice